Proposed new interior design of Rebung Restoran at Menara Atlan, 161B,Jalan Ampang, 50450, Kuala Lumpur for Chef Ismail Ahmad / Nursyafiqah Abas. - Abas, Nursyafiqah (Faculty of Architecture, Planning and Surveying, 2012)
The final project of interior design for final semester students is the representation of studentsunderstanding towards process and important aspects of interior design that has been studies and analyzed from the only the basic knowledge and manage the project to the presentation stage of final design proposal. The Proposal is proposed new interior design of Rebung Restoran,at Menara Atlan, 161B, Jalan Ampang ,50450, Kuala Lumpur for Chef Ismail Ahmad. Thefinal project is to proposed new theme restaurant, at ground floor of Menara Atlan. This is because the client wants to open new branch. Aim for this project is to provide a comfort dining area and become a famous restaurant in Malaysian and international. Theme restaurant is a conceptual restaurant, which needs the space look elegant, luxury and comfort environment. The objectives of this final project are to create new corporate images for this tower, and to attract more customer come and know about this tower and Rebung Restoran. Other than that is to provide a comfort dining area forthis restaurant. The methodology, that include in this final project is based on the interview with client, observation during site visit and based on the references book. These three methods are very useful to complete this final project. Concept for this project is ContemporaryTropical. Contemporary is“belonging to the present times”, tropical is “coming from, found in or typical of the topics”(Oxford, 2012). Using form and color are dynamically combined to achieve simply, minimal and elegant to this area.